Antibiotic resistance and class 1 integron genes distribution in irrigation water-soil-crop continuum as a function of irrigation water sources. (15th November 2021) - Shamsizadeh, Zahra; Ehrampoush, Mohammad Hassan; Nikaeen, Mahnaz; Farzaneh Mohammadi,; Mokhtari, Mehdi; Gwenzi, Willis; Khanahmad, Hossein
Abstract: The increasing demand for fresh water coupled with the need to recycle water and nutrients has witnessed a global increase in wastewater irrigation. However, the development of antibiotic resistance hotspots in different environmental compartments, as a result of wastewater reuse is becoming a global health concern. The effect of irrigation water sources (wastewater, surface water, fresh water) on the presence and abundance of antibiotic resistance genes (ARGs) ( bla CTX-m-32, tet -W, sul 1, cml -A, and erm -B) and class 1 integrons ( intI 1) were investigated in the irrigation water-soil-crop continuum using quantitative real-time PCR (qPCR). Sul 1 and bla CTX-m-32 were the most and least abundant ARGs in three environments, respectively. The abundance of ARGs and intI 1 significantly decreased from wastewater to surface water and then fresh water. However, irrigation water sources had no significant effect on the abundance of ARGs and intI 1 in soil and crop samples. Principal component analysis (PCA) showed that UV index and air temperature attenuate the abundance of ARGs and intI 1 in crop samples whereas the air humidity and soil electrical conductivity (EC) promotes the ARGs and intI 1. So that the climate condition of semi-arid regions significantly affects the abundance of ARGs and intI 1 in crop samples. The results suggest that treated wastewater might be safely reused in agricultural practice in semi-arid regions without a significant increase of potential health risks associated with ARGs transfer to the food chain. However, further research is needed for understanding and managing ARGs transfer from the agricultural ecosystem to humans through the food chain. Graphical abstract: Image 1 Highlights: High numbers of ARGs were detected in wastewater which Sul 1 was the most abundant. There was a difference in abundance of ARGs in different irrigation water sources. ARGs had a similar abundance pattern in different sources irrigated soil and crops. Wastewater irrigation has no significant effect on ARGs abundance in soil and crops. Climate condition affects the abundance of ARGs in crop samples.